Depiction of Narcissistic Motherhood in White Oleander (1999) (EUFONI: Journal of Language, Literary, and Cultural Studies, 2024)
Mother is the first figure that a child sees as beings who have been attached from the pregnancy phase. After an infant is born, another attachment to the mother should become even stronger for more time that they spend together. Therefore, those who grow up with attachment, on the other side of their mothers’ domination, may likely end up with copying the mothers’ characteristics or learnings towards them. In this study, narcissistic motherhood is analyzed towards Astrid Magnussen character in a novel written by Janet Fitch in White Oleander (1999). Therefore, this novel is analyzed by using Miller’s (1990) theory of narcissist psychoanalysis focusing on narcissistic disturbance that makes a descriptive qualitative approach that fits this study. The study shows that as a result of Ingrid’s early narcissistic adaptation towards her daughter, makes Astrid signals narcissistic desires for respect, echoing, understanding, sympathy, and mirroring suffer a very peculiar fate.